University Students’ Perception of the Use of Socrative in Learning Experiences with Mobile Technology - Perera Rodríguez, Víctor Hugo (REDIE es una publicación del Instituto de Investigación y Desarrollo Educativo (IIDE)., 2019)
The growing integration of mobile technology into classrooms is producing new environments that innovate teaching methods. This descriptive, survey-based study analyzes trainee teachers’ perceptions of the use of Socrative and its implications for learning processes. Data was collected through a questionnaire designed ad hoc. The study sample comprised university students (n= 168) from the bachelor’s degree in early childhood education at the School of Education Sciences of a Spanish university. The results of this study indicate significant changes in students’ learning processes, social relations, and teaching methodologies.